Genética de populações de anofelinos IV. Estudos eletroforéticos das populações naturais de Anopheles nuneztovari e Unopheles darlingi. Correlação genética entre espécies - Narang, Sudhir; Santos, Joselita Maria Mendes dos; Garcia, João C.; Cristakou, Helena D.; Narang, Neelam (Acta Amazonica, 1979)
Genetic variation at 26 loci in a natural population of A. nuneztovari and 19 loci of A. darlingi, have been studied by zymogram techniques. Average proportions of polymorphic loci, heterozygous individuals per locus and heterozygosity of individual genomes are 0,54, 0,111 and 0,171 in A. nuneztovari and 0.632, 0,125 and 0,21 in A. darlingi respectively. The degree of genetic variability in each species varies from locus to locus. In general esterases are far more polymorphic than dehydrogenases. A. darlingi has more genetic identity with A. aquasalis (I = 0,624) tham with A. nuneztovari (I = 0,479).